Having a basket full of disease-free tomatoes - Sadashiva, A T; Hanson, Peter; Reddy, M Krishna; Reddy, K Madhavi; Gopalakrishnan, C; Hebbar, Shankar; Ravishankar, K V; Singh, T H; Kumar, M Senthil; Gowda, N S Nage; D’Mello, Dominic (Indian Horticulture, 2019)
Tomato leaf curl disease, bacterial wilt and early blight are serious production constraints in major tomato-growing areas in our country. Scientists of the IIHR, Bengaluru, have developed two high-yielding F 1 hybrids, Arka Samrat and Arka Rakshak which are resistant to all three diseases. Both hybrids have been well adopted by farmers. Tomato growers have doubled their income by adopting these hybrids. In addition to high yield potential, hybrids possess deep red firm fruits with good shelf-life and long distant transportability. The programmes of hybrid seed production and distribution is being done to meet the increasing demand of seeds of both hybrids.